Nicking Endonuclease in Cyanobacteria - Bheemanaik2; Narayanaswamy Anand1, Vinodhini Sundararajan1, Shivakumara (Recent Research in Science and Technology, 2010)
The presence of restriction endonuclease in cyanobacteria is well known but another class of enzyme, the nicking endonuclease, has not so far been reported. We have come across a putative nicking endonuclease from the unicellular cyanobacterium Chroococcus minutus and report this for the first time. 1Centre for Advanced Studies in Botany, University of Madras, Guindy campus, Chennai-600 025, India. 2Department of Biochemistry, Indian Institute of Science, Bangalore 560 012, India Â Â